The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1103/physrevb.41.7192
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of CuO single crystals

Abstract: Raman scattering in single-crystalline CuO samples has been studied. From the polarization dependence, the symmetries of the three Raman-active optical phonons have been identified. The Ag Raman mode with frequency of 290 cm ' was found to be strongly polarized along one of the crystal axes. This suggests that there are cancellations between different components of its Raman tensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
85
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 6 publications
14
85
0
Order By: Relevance
“…There are three acoustic modes (Au + 2Bu), six infrared active modes (3Au + 3Bg), and three Raman active modes (Ag + 2Bg). Three Raman active optical phonons identified were comparable to that reported previously by other methods [31]. The Raman analysis of the CuO sample confirmed the three known bands having intensities of 297, 346 and 631 cm À1 , respectively, which is consistent with the previous findings [32].…”
Section: Resultssupporting
confidence: 91%
“…There are three acoustic modes (Au + 2Bu), six infrared active modes (3Au + 3Bg), and three Raman active modes (Ag + 2Bg). Three Raman active optical phonons identified were comparable to that reported previously by other methods [31]. The Raman analysis of the CuO sample confirmed the three known bands having intensities of 297, 346 and 631 cm À1 , respectively, which is consistent with the previous findings [32].…”
Section: Resultssupporting
confidence: 91%
“…The major peaks observed in the spectrum at 297 and 628 cm −1 , with a shoulder at 343 cm −1 are characteristic for crystalline tenorite CuO. [42][43][44][45] Cu 2 O is expected to show signals at 151, 280 and 650 cm −1 , 45,46 which are not observed here. The broad peak present at 1110 cm −1 is assigned as the second harmonic of the B g mode of CuO at 628 cm −1 .…”
Section: Resultsmentioning
confidence: 54%
“…However, only three (Ag + 2Bg) modes are Raman active [26]. Xu et al [27] observed three Raman bands at 282, 330 and 616 cm −1 for CuO nanomaterial.…”
Section: Resultsmentioning
confidence: 99%